2019
DOI: 10.1038/s41598-019-41817-7
|View full text |Cite|
|
Sign up to set email alerts
|

Implications of the strain irreversibility cliff on the fabrication of particle-accelerator magnets made of restacked-rod-process Nb3Sn wires

Abstract: The strain irreversibility cliff (SIC), marking the abrupt change of the intrinsic irreversible strain limit ε irr,0 as a function of heat-treatment (HT) temperature θ in Nb 3 Sn superconducting wires made by the restacked-rod process (RRP ® ), is confirmed in various wire designs. It adds to the complexity of reconciling conflicting requirements on conductors for fabricating magnets. Those intended for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Since then, different strategies have been developed for evaluating the impact of mechanics in the critical current (I c ) of Nb 3 Sn superconductors [31]. Related to accelerator magnet applications, they range from critical current measurements in full cables (or sub-scale cables) down to single wires, on which the conductor is subjected to the action of a certain type of load [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, different strategies have been developed for evaluating the impact of mechanics in the critical current (I c ) of Nb 3 Sn superconductors [31]. Related to accelerator magnet applications, they range from critical current measurements in full cables (or sub-scale cables) down to single wires, on which the conductor is subjected to the action of a certain type of load [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…The higher Jc of ERMC-1 relative to the MQXF wire is due mostly to its larger sub-element size and the higher ('standard') Sn stoichiometry. The former may not be acceptable for future accelerator magnets [4], and the latter increasingly compromises RRR (or requires a low heat treatment temperature, compromising Bc2 * [10] and strain performance [11]) as the sub-element size is reduced [7]. It has not been tested specifically in the present study, but it is also likely that this contributes to higher local RRR degradation at cable edges than would be obtained for 'reduced tin' wires like MQXF.…”
Section: Discussionmentioning
confidence: 94%
“…Heat treatment optimization to increase RRR or stability sacrifices a large part of the gain in Jc (relative to MQXF). It is therefore likely that the reduced tin formulation would be preferable in these applications, whilst also providing a larger parameter space for heat treatment optimization [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As matter of fact a clear quantitative correlation between voids and mechanical limits was obtained for Bronze route wires 21 while for the other types of internal tin wires, such as RRPs, the correlation has yet to be demonstrated. It was shown that varying the dopants (Ti or Ta) and the temperature of the heat treatment final plateau (600–750 °C), the axial irreversible limit of RRP wire changes 49 . Using the combination of x-ray tomography and unsupervised machine learning algorithm would be possible to completely characterize Nb 3 Sn wires and quantify the impact of the voids variation on the irreversible limit due to the different heat treatments.…”
Section: Discussionmentioning
confidence: 99%